Median lethal Dose and Acute Toxicity of Rosa canina L: In-Vivo Study - Zaman Mahmood Jasim; Ghaith Ali Jasim; Ibrahim Saleh Abbas (College of Pharmacy / Mustansiriyah University, 2022)
Rosa canina belongs to rosacea family. Rosa. canina has a high concentration of phyto-constituents such as flavonoids, carotenoids, triterpene and vitamins as vitamin C, E, and A Rosa canina have an anti-inflammatory and antioxidant   effects. The antioxidant effect belongs to presence of large quantities of phytochemicals such as flavonoids and polyphenols. Rosa canina has been used for arthritis gout, osteoarthritis, urinary tract disorder, diabetes, inflammation and cancer. After grinding the leaves of Rosa canina, they are extracted by using ethanol solvent (cold extraction method), then the extract concentrated by rotary evaporator at 40 c° and leaving it to dry.   Median lethal dose (LD50) has been examined on 84 mice (male and female) divided into seven groups, each one contains 12 (6 male and 6 female). The animals were monitored for signs and any behavior changes after administration of Rosa canina ethanol extract. Acute toxicity study was done on 20 rats (male and female for fourteen days. The weight of animals was taken at day 0, 7, and 14. At day fourteen, relative organ weight as well as histopathological examination for (heart, liver, spleen, kidney, lung, abdominal stomach, testes and ovaries) were taken. In addition to the serum biochemical tests for) blood glucose, urea, creatinine, ALT, AST and total bilirubin (were done at day fourteen. The result of this study, indicated that lethal dose 50 was 16.527 gram/kilogram. Acute toxicity study, revealed that there is no significant difference between relative organ weight of controlled and treated groups for all organs that were selected and mentioned above. In addition, there is no significant difference between serum biochemical tests for both controlled and treated groups. Finally, no changes have been found between controlled and treated groups regarding histopathology examination due to the p value was P ˃ 0.05. Conclusion According to the presented study, ethanol extract of Rosa canina showed wide range of safety depending on the result of lethal dose 50h (16.527 g/kg). Therefore, the extract considered nontoxic. No cytotoxic effect appeared by using ethanol extract of Rosa canina in acute toxicity study. This belongs to the results obtained, which include no significant difference between control and treated male and female rats in biochemistry tests and histopathological examination.